Laktatniveau bei Belastung im Wasser und an Land - Payton, S. J. (Journal of Human Sport & Exercise, 2018)
Water based exercise is a popular medium for exercise for a number of populations from athletic to elderly to post orthopaedic. Many of the physiological variables have been studied on the benefits of aquatic exercise such as reduction in impact, range of motion and heart rate response. One area which has been overlooked is blood lactate (BLac) response to exercise in water. Exercise in water may elicit different physiological responses to blood lactate levels. If the objective is to improve a client`s exercise tolerance, then understanding the physiological difference to exercise in water will enable the clinician/coach to formulate appropriate interventions to enable to use this medium to the benefit of a patient and or an athlete. This study is a systematic review of peer-reviewed papers, which have compared BLac levels during aquatic exercise and land based exercise. A systematic search on a number of peer reviewed search engines resulted in 13 studies.